Coloniality of power and coloniality of the genre: Sentipensar the struggles of indigenous women in Abya Yala from the worlds in relation - Cariño Trujillo, Carmen (2019)
In this work I reflect from the concepts coloniality of power (Quijano, 1992) and gender coloniality (Lugones, 2008) key elements to senti-pensar the struggles of indigenous women in the continent in defense of Buen Vivir in their territories. Women together with their indigenous peoples / nationalities are mobilized for the defense of land-territory-life, this is not a novelty, but in recent years their participation has become more visible as the threat to the territories attentive to fundamental elements in the reproduction of life that had not previously been of interest to Capital. In front of that I am also interested in paying attention to the ways in which the women of the territories build and resist from other ontologies in defense of life. Thinking the reality of our countries from the coloniality of power and the coloniality of gender implies, among other things, starting from the existence of structures of domination, exploitation and extermination that have been reproduced throughout the last five centuries in Abya Yala and that have led to the classification of the world and the pretension of imposition of a world that denies the existence of other worlds that inhabit these territories and that have been persecuted, massacred, in- visibilized but that exist and re-exist (Albán, 2013: 204) in these territories.